Transdermal metformin hydrochloride-loaded cubic phases: in silico formulation optimization, preparation, properties, and application for local treatment of melanoma. (1st January 2019) - Yu, Xiang; Zhou, Wei; Wang, Hongmei; Lu, Sheng; Jin, Yiguang; Fu, Junhui
Abstract: Metformin hydrochloride (Met) is commonly used for antidiabetic therapy though its antimelanoma action is also reported. Conventional oral administration method of Met is not appropriate for therapy of melanoma because of large dose, adverse reactions, and low efficiency. Here, a transdermal Met-loaded cubic phase was developed for local treatment of melanoma. In silico formulation optimization of the cubic phases was done, and the corresponding formulations were prepared and characterized. The optimized formulations were screened based on the stable microstructure and proper fluidity. Highly efficient mouse skin permeability of Met was found with the cubic phases compared to Met solutions. High antimelanoma effect of transdermal Met-loaded cubic phases also was shown by the significant decrease of tumor volume and the improvement of melanoma cell apoptosis on the B16 melanoma mice. Met-loaded cubic phases are a promising topically applied medication for local therapies of melanoma.